A Novel Printable Watermarking Method in Dithering Halftone Images. (30th May 2016) - Lee, Hui-Lung; Chen, Ling-Hwei
Abstract : Halftone images are commonly printed on books, newspapers, and magazines. How to protect the copyright of these printed halftone images becomes an important issue. Digital watermarking provides a solution for copyright protection. In this paper, we will propose a novel printable watermarking method for dithering halftone images. Based on downsampling and the property of a dispersed dithering screen, the method can resist cropping, tampering, and print-and-scan process attacks. In addition, comparing to Guo et al.'s method, the experimental results show that the proposed method provides higher robustness for the above-mentioned attacks and better visual quality in the high-frequency regions of halftone images.